Hubungan antara Kelekatan dengan Orangtua dan Keintiman Dalam Bepacaran pada Dewasa Awal - Cahyaning Utami; Heru Astikasari Setya Murti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2017)
Attachment is a lasting effective bond characterized by a tendency to seek and maintain the closeness of one individual to another, which can provide a sense of security, depending on the quality of the relationship. Based on the quality of the relationship, indivisuals will develop an internal working model that can lasts throughout a lifetime and will likely to affect the intimate relationships during adulthood. The aim of this research was to investigate the relationship between attachment and intimacy in young adults. One hundred and four subjects participated in this research, consisted in early adulthood between the age of 20 to 30 years old, who were in a relationship dating.  The instruments of this research is Inventory of Parent and Peer Attachment (IPPA) scale and Personal Assessment of Intimacy in Relationship (PAIR) scale. The research shows a corelation beetwen parent attachment (mother) and intimacy r = 0,320 p = 0,001 (p<0,05) and corelation of parent attachment (father) with intimacy r = 0,256 p = 0,009 (p<0,05). The result shows a significant positive relationship between parent attachment and intimacy it means thehigher of the attachment then will also higher of intimacy in relatioonship.   Keywords: attachment, intimacy, young adulthood